Numerical Investigation of Crash Energy Distribution of Lightweight Vehicle at Medium and High-Speed Impacts - SUBRAMANI, YOGENDREN; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates how crash energy is distributed in a lightweight vehicle during frontal collisions at 45 km/h and 90 km/h using Finite Element Analysis (FEA) in ANSYS. As there is an increased demand of fuel efficient and environmentally supporting vehicles, the usage of lightweight materials such as aluminum is on the rise. Although these materials add to functioning and productivity, the problems in accidents emerge. The simulation findings indicated that during medium speeds, light weight vehicles are crashworthy, yet during high speeds severe deformation and concentration of stress undermines structural strength. The paper emphasizes the importance of hybrid materials and advanced design reinforcements aiming at the equilibrium between effectiveness and safety of the occupants.